2015
DOI: 10.1007/s12062-014-9108-5
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Memory Ability and Change: (In)Accuracy of Memory Self-Assessments in Relation to Performance

Abstract: Little is known about subjective assessments of memory abilities and decline among middle-aged adults or their association with objective memory performance in the general population. In this study we examined self-ratings of memory ability and change in relation to episodic memory performance in two national samples of middle-aged and older adults from the Midlife in the United States study (MIDUS II in 2005-06) and the Health and Retirement Study (HRS; every two years from 2002 to 2012). MIDUS (Study 1) part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 93 publications
5
33
1
1
Order By: Relevance
“…The daily nature of our study could allow for less bias in retrospective recall. Consistent with past work suggesting that self-ratings of memory abilities were related to memory performance (Rickenbach et al, 2015), our results indicated that cognitive resources were negatively correlated with memory problems, suggesting that those lower in memory abilities actually reported more daily memory problems. For the purposes of this study and the focus on memory problems, episodic memory was chosen as the most relevant measure of cognitive resources.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The daily nature of our study could allow for less bias in retrospective recall. Consistent with past work suggesting that self-ratings of memory abilities were related to memory performance (Rickenbach et al, 2015), our results indicated that cognitive resources were negatively correlated with memory problems, suggesting that those lower in memory abilities actually reported more daily memory problems. For the purposes of this study and the focus on memory problems, episodic memory was chosen as the most relevant measure of cognitive resources.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, we tested whether SOC use moderated the relationship between cognitive resources and/or daily stressors and memory problems. Despite a significant negative bivariate correlation between cognitive resources and memory problems, when controlling for all covariates, neither age nor cognitive resources were associated with memory problems, Past work has found that objective memory performance on tests is not necessarily correlated with memory problems and that adults of all ages complain of memory problems (Jungwirth et al, 2004; Rickenbach et al, 2015; Lachman, 2004; Slavin et al, 2010; Van Bergen et al, 2009). …”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Cognitive aging is inherently a longterm process; cross-sectional analyses were always severely constrained by the inability to distinguish cohort differences from true effects of aging. The article by Rickenbach et al (2015) in this special issue on memory self-assessments would not have been possible in 1994; it uses data collected on up to six occasions over 10 years by the Health and Retirement Study, complemented by rich data including neuroimaging from the Midlife in the United States (MIDUS II) study. Their finding that self-assessment of memory problems and of recent decline in function are very weakly related to actual performance or change in performance; this is a fundamental problem for a health care system which relies overwhelmingly on self-assessment and presentation for diagnosis of cognitive impairment.…”
Section: Introduction To Special Issue For 20th Anniversary Of the Nimentioning
confidence: 99%